Infant Trauma Alters Social Buffering of Threat Learning: Emerging Role of Prefrontal Cortex in Preadolescence - Robinson-Drummer, Patrese A.; Opendak, Maya; Blomkvist, Anna; Chan, Stephanie; Tan, Stephen; Delmer, Cecilia; Wood, Kira; Sloan, Aliza; Jacobs, Lily; Fine, Eliana; Chopra, Divija; Sandler, Chaim; et al. (Frontiers in Behavioral Neuroscience, 2019)
Within the infant-caregiver attachment system, the primary caregiver holds potent reward value to the infant, exhibited by infants’ strong preference for, approach responses and proximity-seeking towards the mother. A less well-understood feature of the attachment figure is the caregiver’s ability to reduce fear via social buffering, commonly associated with the notion of a ‘safe haven’ in the developmental literature. Evidence suggests this infant system overlaps with the neural network supporting social buffering (attenuation) of fear in the adults of many species, a network known to involve the prefrontal cortex (PFC). Here, using odor-shock conditioning in young developing rats, we assessed when the infant system transitions to the adult-like PFC-dependent social buffering of threat system. Rat pups were odor-shock conditioned (0.55mA-0.6mA) at either postnatal day (PN)18 (dependent on mother) or 28 (newly independent, weaned at PN23). Within each age group, the mother was present or absent during conditioning, with PFC assessment following acquisition using 14C 2-DG autoradiography and cue testing the following day. Since the human literature suggests poor attachment attenuates the mother’s ability to socially buffer the infants, half of the pups at each age were reared with an abusive mother from PN8-12. Results showed that for typical control rearing, the mother attenuated fear in both PN18 and PN28 pups, although the PFC [infralimbic (IL) and ventral prelimbic (vPL) cortices] was only engaged at PN28. Abuse rearing completely disrupted social buffering of pups by the mother at PN18. Results from PN28 pups showed that while the mother modulated learning in both control and abuse-reared pups, the behavioral and PFC effects were attenuated after maltreatment. Our data suggest that pups transition to the adult-like PFC social support circuit after independence from the mother (PN28), and this circuit remains functional after early-life trauma, although its effectiveness appears reduced. This is in sharp contrast to the effects of early life trauma during infancy, where social buffering of the infant is more robustly impacted. We suggest that the infant social buffering circuit is disengaged by early-life trauma, while the adolescent PFC-dependent social buffering circuit may use a safety signal with unreliable safety value.